PELATIHAN PUBLIC SPEAKING SEBAGAI DASAR KONSEP PUBLIC RELATIONS BAGI PARA GURU SMA 4 KOTA SERANG UNTUK MENINGKATKAN KUALITAS DAN KETERAMPILAN KOMUNIKASI - Azhar, Intan Nabila; Idzatulloh, Alif; Hidayatullah, Tubagus Ade Rahmat; Suryasuciramdhan, Arfian; Zulfikar, Meiby (Bussman Journal : Indonesian Journal of Business and Management, 2024)
Public Relations (PR) in educational institutions plays a crucial role in maintaining good relationships between schools and the community. By designing good relationships, schools can gain community support and build a positive image. Public Relations in the educational context serves as an important communication tool to provide information about the school to the public. Consequently, the community can better understand the school’s vision, mission, and activities. Training in Public Relations for school administrators is a crucial step to provide understanding and enhance skills in this field. Thus, they can build a positive image of the school to the public and influence the public to choose the school as a favorite. This will help improve the reputation and trust of the community towards the school. The final result of this service is the school’s ability to design effective Public Relations activities. Consequently, policymakers at the school can use these strategies to build a positive image and improve the quality of education, as well as strengthen relationships with the community and other stakeholders